2003
DOI: 10.1097/00045391-200303000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function Assessment by Tissue Doppler Echocardiography in Relation to Hormonal Replacement Therapy in Postmenopausal Women With Diastolic Dysfunction

Abstract: The objective of this study was to evaluate the effect of hormone replacement therapy (HRT) regimens on left ventricular diastolic function by using mitral pulsed wave Doppler (MPWD) and tissue Doppler velocities (TDE). Seventy-eight postmenopausal women with normotensive and impaired diastolic left ventricular filling were included in the study. All the patients began a six-cycle HRT course. This formulation consisted of E2 valerate plus Medroxy progesterone acetate (MPA). Left ventricular diastolic function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, this study is a crosssectional study and therefore does not address the changes in diastolic function parameters before and after HRT. Gökçe et al [15] evaluated LV diastolic function in 78 normotensive healthy postmenopausal women with diastolic dysfunction. In this study, among the conventional Doppler parameters, peak A velocity, DT, and IVRT significantly decreased, while peak E velocity and E/A ratio increased after a 6-month treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study is a crosssectional study and therefore does not address the changes in diastolic function parameters before and after HRT. Gökçe et al [15] evaluated LV diastolic function in 78 normotensive healthy postmenopausal women with diastolic dysfunction. In this study, among the conventional Doppler parameters, peak A velocity, DT, and IVRT significantly decreased, while peak E velocity and E/A ratio increased after a 6-month treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that estrogen supplementation prevented intracellular Ca 2ϩ cycle imbalance (15) and enhanced left ventricular diastolic function in OVX monkeys (77). Previous research also illustrated that estrogen supplementation improved the diastolic function of women with LVDD and animal models of LVDD (39,63,130). Taken together, estrogen balances the Ca 2ϩ homeostasis cycle and improves myocardial diastolic function, thereby reducing the incidence of DDrelated cardiovascular disease in postmenopausal women.…”
Section: Estrogen and Calcium Handling Protein-related Heart Diseasesmentioning
confidence: 91%
“…Moreover, when older women are compared with their agematched male counterparts, the likelihood of manifesting more prominent diastolic dysfunction is increased (32)(33)(34). Findings from small clinical (35)(36)(37)(38)(39) and animal studies, as reviewed by us (40) and others (31,41), document estrogen therapy efficacy in improving diastolic function and/or limiting increases in LV mass and interstitial remodeling after surgically induced or natural menopause. These data affirm estrogen's role in the preservation of diastolic function in the female heart.…”
Section: What Evidence Supports a Role For Estrogen In The Maintenancmentioning
confidence: 96%